2008
DOI: 10.1002/jcb.21979
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Fas and FasL in Taiwan cobra phospholipase A2‐treated human neuroblastoma SK‐N‐SH cells through ROS‐ and Ca2+‐mediated p38 MAPK activation

Abstract: The aim of the present study is to elucidate the signaling pathway involved in death of human neuroblastoma SK-N-SH cells induced by Naja naja atra phospholipase A(2) (PLA(2)). Upon exposure to PLA(2), p38 MAPK activation, ERK inactivation, ROS generation, increase in intracellular Ca(2+) concentration, and upregulation of Fas and FasL were found in SK-N-SH cells. SB202190 (p38MAPK inhibitor) suppressed upregulation of Fas and FasL. N-Acetylcysteine (ROS scavenger) and BAPTA-AM (Ca(2+) chelator) abrogated p38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…At the same time, a decrease in intracellular calcium cancelled ouabain's effects on p38 and JNK phosphorylation, allowing us to assume these processes to be calcium dependent. This corresponds to previously reported data …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…At the same time, a decrease in intracellular calcium cancelled ouabain's effects on p38 and JNK phosphorylation, allowing us to assume these processes to be calcium dependent. This corresponds to previously reported data …”
Section: Discussionsupporting
confidence: 93%
“…To determine the role of calcium we used Ca 2+ chelator BAPTA‐AM at a concentration of 10 μM which had been previously used in neurons . We showed that BAPTA‐AM did not cancel ouabain‐induced ERK1/2 phosphorylation increase, but instead caused an additional activating effect on ERK1/2 which corresponded well to earlier published data . This allows us to conclude that ouabain‐induced ERK1/2 phosphorylation is not calcium dependent.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was reported that ROS could play a role in downregulating Bcl-2 [32] as well as in triggering the release of cytochrome C from the mitochondria into the cytoplasm along with Fas associated proteins recruitment and finally leading to the activation of caspase 3 and apoptosis [3335]. In our present study, increased levels of ROS in the treatment group indicated that the apoptotic mode of cell death induced by the methanolic fraction of S. grandiflora is through the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have recently reported that BD induces apoptosis in pancreatic cancer cells by activating the phosphorylation of p38-mitogenactivated protein kinase (MAPK) (Lau et al, 2009). Although the function of ROS in the activation of p38-MAPK (Yi et al, 2004;Lee et al, 2008;Chen et al, 2009), and the regulation of NF-kB activity (Hayakawa et al, 2003;Fujioka et al, 2004), has been characterised in substances-induced apoptosis in various cancer cells, the involvement of ROS in BD-induced pancreatic cancer cell apoptosis is yet to be elucidated. Given that ROS have an important function in an array of biological responses and diverse signalling pathways, we hypothesised that BD activates pro-apoptotic pathways through the enhancement of ROS production and the inhibition of NF-kB activity in pancreatic cancer cells.…”
mentioning
confidence: 99%